PENGARUH KINERJA KEUANGAN DAN KARAKTERISTIK DAERAH TERHADAP PENYAJIAN LAPORAN KEUANGAN PEMERINTAH DAERAH MELALUI INTERNET - Priyastiwi, Priyastiwi; Saputra, Nunung (JURNAL RISET MANAJEMEN SEKOLAH TINGGI ILMU EKONOMI WIDYA WIWAHA PROGRAM MAGISTER MANAJEMEN, 2019)
The purpose of this research is to analyze the effect of local government financial performance and their characteristic on the degree of their voluntary reporting of financial statements on the internet. Local government financial performance are measured by intergovernmental revenue, local government expenditure, local government assets, and leverage. While the local government characteristic is income per capita. The samples are financial statement of local government in DIY and Central Java. A total of 40 financial statements are 5 from financial statements form DIY and 35 financial statements form Central Java. The research analysis used multiple regression analysis. The results of this study show the performance financial are intergovernmental revenue, local government expenditure, local government assets have significant positive effect on degree of their voluntary reporting of financial information on the internet, while leverage have significant negative effect. On the otherhand income per capita has no effect on degree of their voluntary reporting of financial information on the internet